Population structure of Hepatus pudibundus (Decapoda: Calappidae) in Fortaleza Bay, Brazil - Medina Mantelatto, Fernando Luis (Universidad de Costa Rica, 1995)
The population of Hepatus pudibundus crabs in Fortaleza Bay, Ubatuba (Sao PauJo), was studied with emphasis on structural aspects such as sex-ratio, size, and reproductive time, based on the number of ovigerous females and on seasonal distribution. Crabs were sampled monthly from November 1988 to October 1989 using a shrimp fishing boat equipped with two otter-trawJs. A total of 405 specimens (males: 133 adult and 34 immature; females: 175 adult, 19 ovigerous and 44 immature) were sampled. Mean animal size, based on the measurement of carapace width (CW), was 53.27 ± 10.59 mm for males and 46.7 ± 7.86 mm for females. Individual size frequency distribution was bimodaJ and skewed to larger size classes in males, and unimodal and normal in females, with the largest numbers occurring in March (83), May (70) and July (50). Reproduction occurred throughout the year, with a high incidence of ovigerous fernales from January to April 1989. The large number of fernales was probably due to the reproductive strategy of the species. The heterogeneous seasonal distribution was probably related to migration to other areas (open sea, estuaries) because of environmental conditions or particular demands during the developmental phase.